Plasma Branched-Chain Amino Acid Concentrations and Glucose Homeostasis in Kidney Transplant Recipients and Candidates - Prasad, G. V. Ramesh; Nash, M. M.; Yuan, W.; Beriault, D.; Yazdanpanah, M.; Connelly, P. W. (Canadian journal of kidney health and disease, 2023)
Background: Post-transplant diabetes mellitus (PTDM) encompasses new-onset and previously unrecognized type 2 diabetes. Kidney failure masks type 2 diabetes. Branched-chain amino acids (BCAA) are closely associated with glucose metabolism. Therefore, understanding BCAA metabolism both in kidney failure and after kidney transplantation may inform PTDM mechanisms. Objective: To understand the impact of present or absent kidney function on plasma BCAA concentrations. Design: Cross-sectional study of kidney transplant recipients and kidney transplant candidates. Setting: Large kidney transplant center in Toronto, Canada. Measurements: We measured plasma BCAA and aromatic amino acid (AAA) concentrations in 45 pre-kidney transplant candidates (15 with type 2 diabetes, 30 without type 2 diabetes) and 45 post-kidney transplant recipients (15 PTDM, 30 non-PTDM), along with insulin resistance and sensitivity by 75 g oral glucose loading for those in each group without type 2 diabetes. Methods: Plasma AA concentrations were analyzed using MassChrom AA Analysis and compared between groups. The insulin sensitivity for oral glucose tolerance tests or Matsuda index (a measure of whole-body insulin resistance), Homeostatic Model Assessment for Insulin Resistance (a measure of hepatic insulin resistance), and Insulin Secretion-Sensitivity Index-2 (ISSI-2, a measure of pancreatic β-cell response) was calculated from fasting insulin and glucose concentrations, and compared with BCAA concentrations. Results: Each BCAA concentration was higher in post-transplant subjects than pre-transplant subjects (P < .001 for leucine, isoleucine, valine). In post-transplant subjects, each BCAA concentration was higher in PTDM versus non-PTDM (odds ratio for PTDM 3-4 per 1 SD increase in BCAA concentration, P < .001 for each). Tyrosine concentrations were also higher in post-transplant subjects than pre-transplant subjects, but tyrosine did not differ by PTDM status. By contrast, neither BCAA nor AAA concentrations were different in pre-transplant subjects with or without type 2 diabetes. Whole-body insulin resistance, hepatic insulin resistance, and pancreatic β-cell response did not differ between nondiabetic post-transplant and pre-transplant subjects. Branched-chain amino acid concentrations correlated with the Matsuda index and Homeostatic Model Assessment for Insulin Resistance (P < .05 for each) only in nondiabetic post-transplant subjects—not in nondiabetic pre-transplant subjects. Branched-chain amino acid concentrations did not correlate with ISSI-2 in either pre-transplant or post-transplant subjects. Limitations: The sample size was small, and subjects were not studied prospectively for the development of type 2 diabetes. Conclusions: Plasma BCAA concentrations are higher post-transplant in type 2 diabetic states, but do not differ by diabetes status in the presence of kidney failure. The association of BCAA with measures of hepatic insulin resistance among nondiabetic post-transplant patients is consistent with impaired BCAA metabolism as a characteristic of kidney transplantation.